Eye problems in a woman with Churg-Strauss syndrome. Issue 2 (February 2017) - Pierce, Benjamin D.; Donald, Carrlene B.; Mendez, Anthony P.
Abstract : ABSTRACT: Churg-Strauss syndrome is a rare, systemic vasculitis of unknown cause. Ocular involvement is a rare but established complication and can lead to vision damage or blindness if not treated promptly. Treatment of ocular manifestations corresponds with systemic treatment of the disease and consists primarily of corticosteroids.